2004
DOI: 10.1111/j.0307-6970.2004.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

A molecular phylogenetic analysis of the pleasing fungus beetles (Coleoptera: Erotylidae): evolution of colour patterns, gregariousness and mycophagy

Abstract: Abstract.  Phylogenetic relationships of Erotylidae (pleasing fungus beetles) were inferred based on DNA sequence data. Relationships of clades within Erotylidae were examined, as was the relationship of the entire family to Languriidae (lizard beetles). 18S and 28S ribosomal DNA were sequenced for sixty‐one taxa representing major erotylid lineages and outgroups. Phylogenetic analyses under varying parameter settings using standard parsimony and likelihood techniques were performed. These data indicate a para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
39
1
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 24 publications
4
39
1
6
Order By: Relevance
“…Unfortunately, these disciplines have a bimodal distribution of interests and rarely intersect: publications on beetle iridescence have appeared either in entomological literature without optical context (e.g. Pope & Hinton 1977;Robertson et al 2004;Doberski & Walmesley 2007) or in the physics literature without a strong organismal context (e.g. Parker 2000Parker , 2002Goldstein 2005;Parker & Martini 2006;Jewell et al 2007b;Vukusic et al 2007;Kinoshita et al 2008;Liu et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, these disciplines have a bimodal distribution of interests and rarely intersect: publications on beetle iridescence have appeared either in entomological literature without optical context (e.g. Pope & Hinton 1977;Robertson et al 2004;Doberski & Walmesley 2007) or in the physics literature without a strong organismal context (e.g. Parker 2000Parker , 2002Goldstein 2005;Parker & Martini 2006;Jewell et al 2007b;Vukusic et al 2007;Kinoshita et al 2008;Liu et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This long-standing confusion can be extremely detrimental when the word iridescence is used to connote a diagnostic character in taxonomic works or treated as a single homologous character state in cladistic analyses (e.g. Robertson et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Larvae and adults of the erotylid subfamily Erotylinae (the remaining subfamilies comprise the former Languriidae, which are phytophagous) and members of Cisidae are exclusively associated with various Polyporales and related higher fungi (Leschen 2003;Robertson et al 2004;Lawrence 1973); they are used as nutrition as well as breeding substrate. The role of volatile compounds involved in host recognition and selection is poorly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…These figures refer to a revised concept of Erotylidae, which also includes the languriids: Recent morphology-and molecular-based phylogenetic studies have shown that the former 'Languriidae' is paraphyletic with respect to the former 'Erotylidae' (Węgrzynowicz 2002;Leschen 2003;Robertson et al 2004), and the latter is now ranked as a subfamily 'Erotylinae' of an expanded Erotylidae. The former separation of these two groups was primarily based on their different biology, with 'Erotylidae' being mycophagous and 'Languriidae' being phytophagous.…”
Section: Introductionmentioning
confidence: 99%